2019
DOI: 10.35584/melysa.v1i2.30
|View full text |Cite
|
Sign up to set email alerts
|

The total plate count of beras kencur herbal medicine in sub-district market Tulungagung city 2018

Abstract: Herbal medicine is a traditional drink made from natural ingredients for human health and is made with methods and equipment that are easier in its simplicity which often does not pay attention to hygiene factors and can be a medium for disease transmission. Based on the Regulation of the Head of the Republic of Indonesia Drug and Food Control Agency No. 12 of 2014 concerning requirements for drug fluids in the form of microbial contamination / ALT ≤104 colonies/ml. The purpose of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Then, based on the requirements of BPOM number 32 of 2019 for the TPC value to meet the requirements, there is<10 CFU/g. The total plate count (TPC) is one of the safety parameters of traditional medicine that is used as a guide to what level of manufacture of the product in implementing Good Manufacturing Practices of Traditional Medicine (CPOTB) [9]. The result of microbiological quality analysis by TPC of instant powder and liquid medicine of red ginger similar to the ginger product produced by Arifan et al that showed the total microbial value match the BPOM and SNI standard [10].…”
Section: Total Plate Count Numbermentioning
confidence: 99%
“…Then, based on the requirements of BPOM number 32 of 2019 for the TPC value to meet the requirements, there is<10 CFU/g. The total plate count (TPC) is one of the safety parameters of traditional medicine that is used as a guide to what level of manufacture of the product in implementing Good Manufacturing Practices of Traditional Medicine (CPOTB) [9]. The result of microbiological quality analysis by TPC of instant powder and liquid medicine of red ginger similar to the ginger product produced by Arifan et al that showed the total microbial value match the BPOM and SNI standard [10].…”
Section: Total Plate Count Numbermentioning
confidence: 99%
“…Vol 01 N 2022, pp 1-6 e-ISSN: XXXX-XXXX DOI: https://doi.org/10.54482/EXTRATERITORIAL/ PHARMACOLOGICAL ACTIVITIES OF KENCUR PLANT (KAEMPFERIA GALANGA L.) AS AN ASMA AND ANTI BACTERIAL MEDICINE oils, are a group of terpenoids, especially monoterpenoids and sesquiterpenoids which are volatile at room temperature and have a distinctive aroma[4].…”
mentioning
confidence: 99%